A qualitative and dynamic exploration of multiple vital uses of ICTs among refugees - Kloetzer, Laure; Womersley, Gail (My University, 2017)
Mobile communities have long been known in the social sciences as early adopters and innovative users of information and communication technologies (ICTs) (Broadbent, 2012; Benitez, 2006; Horst, 2006; Ros et al., 2007), allowing them to maintain transnational ties within and beyond family networks and stay connected to the cultural and political life of multiple countries. Specifically, ICTs have played various new, critical roles in the “migration crisis”: as stated by the convenors, “Internet, GPS and social media become important migratory resources for populations on the move.” We propose a qualitative, dynamic exploration of ICTS among precarious migrants. We highlight how they function as symbolic, cultural and material resources (Bruner, 1991) drawn upon by ‘online,’ ‘connected’ migrants to negotiate bureaucratic uncertainty, share important practical information, navigate local situations and maintain a sense of social identity. Thus, we explore the myriad and complex adaptive uses and responses to the dynamic changes and challenges in institutional and social systems which define modern migration (Ratcliff & Rossi, 2015), and how these uses evolve over time. We argue that ICTs open a methodological window into a better understanding of the trajectories, activities, networks and experiences of precarious migrants. Our main data is drawn from the first phase of an 18-month long research intervention in a centre for Victims of Torture in Athens, Greece, which included 60 qualitative interviews with humanitarian actors, individual migrants followed over time and refugee community leaders. This is complemented with examples from an educational project conducted within Za’atari camp, Jordan. References Benítez J.L. (2006). Transnational dimensions of the digital divide among Salvadoran immigrants in the Washington DC metropolitan area. Global Networks 6 (2): 181-199. Broadbent, S. (2012). Approaches to personal communication. Digital anthropology, 127-145. Bruner, J. (1991). The narrative construction of reality. Critical inquiry, 18(1), 1-21. Horst H. 2006. The Blessings and Burdens of Communication: Cell Phones in Jamaican Transnational Social Fields. Global Networks 6 (2): 143-159. Ratcliff, B. G., & Rossi, I. (2015). Santé mentale et sociétés plurielles. Alterstice-Revue Internationale de la Recherche Interculturelle, 4(2), 3-12. Ros A, Gonzalez E, Marin A, and Sow P. 2007. Migration and information flows: A new lens for the study of contemporary international migration. Barcelona: Internet Interdisciplinary Institute.
, IMISCOE Annual Conference 2017, Rotterdam, Netherlands
Keywords: ICTS Refugees Qualitative